ALL IN ONE SYSTEM (Pendekatan dan Prinsip Psikologis Pengajaran Bahasa Arab Terintegrasi) - Muhammad Rusydi Rasyid (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2009)
Learning a language particularly Arabic may at first sight look complex, demanding and time consuming. That is why Mukti Ali, the former Minister of Religious Affair, has come up with the idea of having several points of entry to language approach, called All in One System. Teaching Arabic as a Foreign Language—with appropriate techniques—to students who are not native speakers will enable them to learn Arabic effectively. It firstly develops a curri-culum for Islamic secondary learners. This approach—All in One System—asserts that to create an effective teaching program it is not enough merely to use the most sophisticated technology such as CD's, and phonetics software. Teaching methods tested in actual conditions are even more important. The process for teaching Arabic to non native speakers is very different from teaching other languages. Therefore, the concept built on teaching Arabic to introduce integrated four skills at once—listening, reading, speaking, and writing is of great importance.